Psychosis as Eluding Agency: Perspective of Phenomenological Psychopathology - Baranovaitė, Kristina (Problemos, 2024)
In the context of the current renewal of phenomenological psychopathology, the article presents one of its fundamental assumptions – the need to meaningfully incorporate experiences of a subject who has encountered pathology into their life narrative. It discusses how, as psychosis progresses, the subject gradually loses agency of their attention and meaning-making. With the help of the novel Cosmos by Witold Gombrowicz, an episode of the active phase of psychosis is reconstructed – in the beginning, the central objects structuring the subject’s attention establish themselves as if independently of the subject. As the delusional system, created on such a basis, expands, it becomes more and more difficult for the subject to preserve the relation with the surrounding world. Creating a narrative in such a situation comes forth as a self-healing effort – an attempt to meaningfully incorporate episodes of altered experience back into one’s realm of agency. For this reason, it is emphasized that, in psychotherapy, it is important not to try to replace the subject’s narrative with a rationalized narrative created by the therapist, but rather to involve the subject in a cooperative dialogue about the personal meaning of their lived experiences.
Keywords: phenomenological psychopathology; psychosis; narrative; agency